Classroom observation in second language classrooms: bridging the gap between theory and practice for pre-service and in-service teachers of Greek as an L2 - Iakovou, Maria (CLIL. Journal of Innovation and Research in Plurilingual and Pluricultural Education, 2020)
This paper is a qualitative study in the framework of a broader project (LETEGR2) that aims to shed light on the way classroom-based observation might contribute to bridging the gap between teaching theory and practice and assisting teacher education. It draws on data derived from pre-service (n=15) and in-service teachers (n=6) who applied the LETEGR2 Classroom Observation protocol in second language classrooms in Greece. Both groups of data are presented according to the observation stages (pre- and post-) in which they have been collected. They are discussed as pre- and in-service teachers’ “voices” in terms of the main issues they bring to the fore in relation to L2 learners’ profiles, the teaching process and teachers’ practices. An attempt is made to link both group of participants’ observed behaviours and events to underlying theoretical concepts for second language learning and teaching.